(7+6) + 9. That is the correct answer
If f(x) = (3x + 7)²
then f(1) = (3(1) + 7)²
= 10²
⇒ f(1) = 100 [OPTION E]
Your method is completely correct. The first term will be 6 and each subsequent term can be obtained by adding 6 to the previous one, meaning the common difference is 6. The number of terms is given by the highest number that is divisible by 6 and dividing it by 6; that is 996/6 = 166
Then we simply apply the formula for arithmetic sequence sum:
S = n/2 [2a₁ + (n - 1)d]
S = 166/2 [ 2(6) + (166 - 1)6]
S = 83,166
So she divided the 2/3 between 4 friends.
So each friend got 2/3 divided by 4, which gives:
(2/3)*(1/4) = 2/12 = 1/6